Design and parameter optimization of flexible comb-type grass seed metering device - Song, Yang; Shumin, Zhang (International Journal of Agricultural and Biological Engineering, 2015)
In order to optimize the structure schema of flexible comb-type grass seeder, the effects of combing teeth gap L, rotation speed of comb shaft N, seed metering device inclining angle α and groove strip inclining angle θ on the rate and uniformity of seeding were observed by test and analyzed, then the coefficient of seeding stability variation was explored in the simulating planting environment on the soil tank test bed based on the above four influencing factors, with Festuca arundinacea seeds as example. According to the results of regression analysis, the model fits well with the actual situation. L, N, α, and the interaction term of N and θ are significant, and the interaction term of θ and α is extremely significant. The analysis of interaction factor effect shows that the variation coefficient responds to the interaction of N and θ in the same manner as that responds to the interaction of θ and α, showing ‘saddle’ variation tendency. Suppose the acceptable maximum value of coefficient of seeding uniformity variation is 4%, then the inverse proportion relationship between factors is inferred according to the change trend of the above interaction factors and derivation of regression equation. Then the regression equation was simplified according to the inverse proportion equation, and four groups of parameters were obtained. Each parameter group was tested, and the test results agreed with the regression equation’s predicting value, with the correlation coefficient 0.726. This research can provide reference for the development of seed metering devices and grass seeders.DOI: 10.3965/j.ijabe.20150801.002Citation: Yang S, Zhang S M. Design and parameter optimization of flexible comb-type grass seed metering device. Int J Agric & Biol Eng, 2015; 8(1): 9－16.